2008
DOI: 10.1021/bm800639w
|View full text |Cite
|
Sign up to set email alerts
|

Ring-Shaped Assembly of Microtubules Shows Preferential Counterclockwise Motion

Abstract: In this paper, we reveal that microtubules (MTs), reconstructed from tubulin in vitro in the presence of guanosine-5'-triphosphate (GTP), have a ring or spiral shape on a motor protein-fixed surface, and these MTs show biased motion in the counterclockwise direction. By cross-linking these MTs during the sliding motion, we obtained large ring-shaped MT assemblies, 1 approximately 12.6 microm in diameter. The ratio of the rings rotating in the counterclockwise direction to those rotating in the clockwise direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
82
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 22 publications
3
82
2
Order By: Relevance
“…2-fold higher flexural rigidity [ref. 40,41]. Using GMPCPP-MTs, the MT bundles were successfully formed.…”
Section: Integration Of the Gliding Mtsmentioning
confidence: 99%
“…2-fold higher flexural rigidity [ref. 40,41]. Using GMPCPP-MTs, the MT bundles were successfully formed.…”
Section: Integration Of the Gliding Mtsmentioning
confidence: 99%
“…In this study, as shown in Fig. 8, an MT with a left-or right-handed supertwist shows axial rotation when moving over processive motor protein 18 . This axial rotation is assumed to be superimposed on the linear motion, generating a torque on the MT that leads to bending of the front segment of MT.…”
Section: Resultsmentioning
confidence: 54%
“…As shown in this figure, any obvious change in the distribution of the inner diameters of the rings moving CCW and CW cannot be found. Previously, it was shown that on a kinesin-coated surface, the direction of the rotational motion of ring-shaped MT assemblies could be tuned from CCW to CW by using structure-controlled MTs 16,18 .…”
Section: Resultsmentioning
confidence: 99%
“…interaction to prevent the sliding of the MTs 31 . In this case also MTs were assembled into rings, but unlike the rings produced at the air-buffer interface, MTs in those rings had no chance of sliding past each other due to strong binding between St and Bt.…”
mentioning
confidence: 99%